Germany’s dual education system: The assessment by its subjects - A. Yu. Pleshakova (Obrazovanie i Nauka)
Introduction. The dual system of VET, widely practiced and popular in Germany, serves as a model for the European Union. The effectiveness of such training, successfully combining the development of theoretical knowledge with the practical activities of students, has been tested by life and time. The indisputable advantages of this system include its ability to respond quickly to the challenges of globalisation and transformation in the world of professions. In this regard, it is very important to address the socio-cultural and historical backgrounds of the dual system formation and to find out the reasons for its successful contemporary functioning.The aim of the present publication was to comprehend the implementation experience of theGermany’s dual system based on the opinions analysis of experts and participants of the dual education system and the feedback from the direct participants of the educational process about this method of acquiring a profession and building a career path.Methodology and research methods. The leading research methods were questionnaire survey, comparative analysis and content analysis of empirical materials. Processing and generalisation of the detailed answers of respondents were based on the inductive method.Results. Historical, mental, socio-economic prerequisites for the appearance and formation of the Germany’s dual education system were identified and described. The methodology and methodological tools for the comparative analysis of attitudes of educational process members (students, practitioners, experts) and their points of view concerning degree of rationality, expediency and efficiency of support and development of dual forms of vocational education. The obtained data and synthesis of evaluative judgments of informants allow us to present an objective picture of the considered option for providing the country’s economy with the necessary labour resources.Practical significance. The materials of the article, confirming the prospects of the introduction and dissemination of the experience accumulated inGermany on the reproduction of skilled workers of enterprises, can be useful for understanding the directions of VET in other countries. Moreover, the research materials can be practically applied for the selection and creation of effective, similar to the German, mechanisms of rapid response to globalisation changes in the manufacturing sector.